Perpetrating Violence Increases Identification With Violent Groups: Survey Evidence From Former Combatants. (July 2018) - Littman, Rebecca
Heightened group identification motivates individuals to perpetrate violence, but can perpetrating violence—in and of itself—increase identification with violent groups? I test this idea using archival surveys of ex-combatants. In Liberia, where many combatants joined their violent group willingly, the data show a positive association between perpetrating violence and identification with one's violent group (Study 1). These results hold even when controlling for potentially confounding variables such as being abducted into the group versus joining willingly, length of time in the group, and personally experiencing violence. Study 2 replicates and extends this finding with data from ex-combatants in Uganda who were abducted into their group, using a natural experiment in which some abductees were forced to perpetrate violence whereas other abductees were not. These findings support a cycle of violence in which perpetrating violence increases identification with violent groups and heightened identification increases future violent behavior.